South African perspectives on the Pentateuch between synchrony and diachrony - Le Roux, J. H.; Otto, Eckart (Library of Hebrew bible/Old Testament studies, 2007)
Setting the scene : the battle of the signs / Jurie le Roux -- A hidden truth behind the text or the truth of the text at a turning point in biblical scholarship two hundred years after De Wette's Dissertatio critico exegetica / Eckart Otta -- The pivotal meaning of Pentateuch research for a history of Israelite and Jewish religion and society / Eckart Otto -- Methodology and exegesis : the tools-and what they are designed for / Gerda de Villiers -- Old Testament between diachrony and synchrony : two reasons for favouring the former / Christo Lombaard -- The blessings in Genesis 49 and Deuteronomy 33 : awareness of intertextuality / Hans Ulrich Steymans -- Reading the Pentateuch with both eyes open : on reading biblical texts multidimensionally / Louis Jonker -- Changing paradigms : Old Testament scholarship between synchrony and diachrony / Alphonso Groenewald -- Criticism of government : Deuteronomy 17:14-20 between (and beyond) synchrony and diachrony / Eben Scheffler -- Will synchronic research into the Pentateuch keep the scientific study of the Old Testament alive in the RSA? / Izak J.J. Spangenberg -- Synchrony, diachrony and reality : the anti-realist ontological implications of theological pluralism in the Pentateuch / Jaco W. Gericke -- Iconographical evidence for a theory on astral worship in seventh and sixth century Judah / Frances Klopper -- Synchrony and diachrony in apocalyptic studies / Pieter M. Venter.W